2020
DOI: 10.1016/j.jtumed.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the vulnerability of frontline nurses to COVID-19 and its impact on perceived stress

Abstract: Objectives This study aimed at exploring and comparing the vulnerability to COVID-19, demographic variables and perceived stress of frontline nurses. Methods This study employed a quantitative comparative-correlational approach. Using the snowball sampling technique, we conducted this study involving 176 frontline nurses from hospitals of the Hail region, KSA. Results The frontline nurses showed high perceived infectability (x = 4.36) and ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 18 publications
5
25
4
1
Order By: Relevance
“…Most of the 86 studies applying a cross-sectional study design assessed the psychological impact at a single point in time. Namely, 29 studies performed data collection in earlier phases of the outbreak in the respective country [64-66, 77, 79-81, 84-89, 91, 96, 98, 100, 103, 105, 106, 108, 109, 111-115, 120, 126], nine during the outbreak [69, 73, 82, 95, 97, 101, 110, 118, 125], 32 in later phases [41, 42, 44-46, 50, 53, 54, 56, 59-61, 67, 68, 70-72, 74, 78, 83, 90, 92-94, 102, 104, 107, 117, 119, 121, 122, 124], and eight after the end of the outbreak [47-49, 52, 57, 58, 63, 99]. Another seven studies focusing on SARS [43, 51, 55], MERS [64], and COVID-19 [75, 76, 123] also included follow-up data.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the 86 studies applying a cross-sectional study design assessed the psychological impact at a single point in time. Namely, 29 studies performed data collection in earlier phases of the outbreak in the respective country [64-66, 77, 79-81, 84-89, 91, 96, 98, 100, 103, 105, 106, 108, 109, 111-115, 120, 126], nine during the outbreak [69, 73, 82, 95, 97, 101, 110, 118, 125], 32 in later phases [41, 42, 44-46, 50, 53, 54, 56, 59-61, 67, 68, 70-72, 74, 78, 83, 90, 92-94, 102, 104, 107, 117, 119, 121, 122, 124], and eight after the end of the outbreak [47-49, 52, 57, 58, 63, 99]. Another seven studies focusing on SARS [43, 51, 55], MERS [64], and COVID-19 [75, 76, 123] also included follow-up data.…”
Section: Resultsmentioning
confidence: 99%
“…We retrieved 1,640 records from the electronic databases (after removal of duplicates) and 355 from the additional searches. After screening of title and/or abstract, we assessed 417 full texts for eligibility, of which 331 were excluded for a variety of reasons (e.g., mismatch with inclusion criteria, mixed population, wrong focus), and 86 [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature has shown that, compared to other professionals, healthcare providers, especially nurses, have a higher risk of developing emotional distress like depression, anxiety, and burnout due to work-related stress [ 25 ]. Moderate stress was also evident among frontline nurses in Saudi Arabia who were highly perceived infectability to COVID-19 and germ aversion [ 26 ]. There are factors that appeared to increase the risk of developing anxiety symptoms among Chinese nurses, like poor nurse-patient relationships, over-commitment, and lower job rank [ 27 ].…”
Section: Discussionmentioning
confidence: 99%